Dampak Penggunaan Media Sosial terhadap Gangguan Psikologis Mahasiswa - Reva Diena Mustaqina; Sri Mulyeni (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Social media is one form of technological advancement that has become an integral part of students’ lives, including university students. Its use is not limited to communication and information sharing, but it may also generate psychological effects that influence both physical and mental health. The purpose of this review is to identify and explain the psychological impacts of social media use through appropriate theoretical approaches, which serve as a foundation for discussing the research findings. This study employs a literature review method by examining various academic books and relevant scientific articles. The findings indicate that excessive use of social media has the potential to cause psychological problems among university students, such as social comparison behavior, cyberbullying, decreased sleep quality, and reduced learning productivity. These issues are influenced by several factors, including the intensity of social media use, the type of content accessed, and individuals’ ability to manage emotions and time. Furthermore, uncontrolled social media use may lead to difficulties in social relationships, increased procrastination, poor time management, and reduced self-control in using social networking platforms. Therefore, students are encouraged to develop healthier patterns of social media use to reduce the risk of psychological disturbances. This review is also expected to assist healthcare professionals in understanding the relationship between the intensity of social media use and the occurrence of depressive symptoms among university students.